The Interaction Between Personality and Health Policy: Empirical Evidence from the UK Smoking Bans - Cecily Josten; Grace Lordan (Institute of Labor Economics (IZA), 2020)
We investigate whether responses to the UK public places smoking ban depend on personality. Drawing on individual level panel data from the British Household Panel Survey (BHPS) we exploit variation in the timing and location of these bans to establish their overall effect on smoking outcomes, and how this differs by personality. We measure personality using the Big Five personality traits. We are particularly interested in conscientiousness, given the evidence that it is a good proxy for self-control. Overall, we find that a one standard deviation increase in conscientiousness leads to a 1.4 percentage point reduction in the probability of smoking after the ban. Notably, this is the only Big Five personality trait that interacts with the smoking ban. This finding is very robust to different specifications.
Keywords: C23; D04; I10; I12; I18; H75; 330; smoking ban; personality; Five Factor Model; conscientiousness